The need for compliance with comprehensive reparation in cases of domestic violence from the Comprehensive Organic Criminal Code in Ecuador - Enríquez Palate, Ivonne Magdalena (2024)
Domestic violence, historically linked to social factors such as patriarchy, has been recognized in Ecuador as a relevant problem within the constitutional and criminal sphere, especially in Article 159° of the Comprehensive Organic Criminal Code (COIP), which regulates violence against women and members of the family, addressing psychological, sexual and physical aggressions that seriously affect the quality of life of the victims. This article analyzes the adequacy of comprehensive reparation in domestic violence proceedings based on the COIP, using a methodology of doctrinal and jurisprudential review. It highlights reparation measures, such as economic compensation and psychological therapy, included in the sentences, although it is noted that the scope of such measures is still under debate in Ecuador. This study seeks to contribute to the critical analysis of the effectiveness of these legal tools to guarantee the restitution of victims' rights.